PENGARUH METODE ROLE PLAYING TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA KELAS III DI SEKOLAH DASAR - Sri Nengsih, Shinta Purwani; Sabri, Tahmid; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to learn more about the influence of the role playing method on the learning outcomes of citizenship education in the third grade students of 12 Elementary Schools in Pontianak City. The method used to experiment with the Quasi Experimental design and control group design is not equivalent. The population of all students is 41 people. The sample of this study was class IIIA students who were directed by 20 people as an experimental class and class IIIB students as an intellectual control class reached 21 people. The data technique used is measurement techniques and data collection from student learning outcomes tests. Based on data analysis, the average post-test results of the experimental class were 73.25 and the control post test at the mean of 67.24. Hypothesis test results using t-test (surveyed variance) get a count of 2.170 t = as for the level of freedom (20 + 21-2 = 39) with a significant level ? = 5% obtained t = 1.669 tables, which means t count> t table, This proves that there is an effect of using role playing methods on the learning outcomes of civic education. Based on the results of the effect measurement (ES) get ES = 0.612 Which includes the secondary criteria. Keywords: Influence, Learning Outcomes, Role Playing Methods, Citizenship Education Learning.